A rare case of fusiform celiac artery aneurysm after penetrating trauma. (2018) - Shariff, Abdullah; Skinner, Ruby; Pakula, Andrea
Highlights: Celiac artery aneurysm make up a small number of visceral artery aneurysms. Penetrating trauma is a common cause of visceral artery aneurysms. Endovascular management is becoming commonplace for these lesions. Abstract: Introduction: Visceral artery aneurysms are an uncommon clinical problem with aneurysms of the celiac artery only making up a small percentage of all visceral artery aneurysms. The more common splenic and hepatic aneurysms are often symptomatic with pain or rupture and associated hemorrhage. Presentation of case: We present a case of an otherwise healthy 30 yo male with an asymptomatic, posttraumatic arterial aneurysm of the celiac artery. He initially presented to our trauma center after sustaining multiple gunshot wounds which required multiple abdominal surgeries. He represented four weeks later with 3 days of flank pain and fever. Extensive workup yielded an incidental finding of 14 mm fusiform aneurysm of the celiac artery with associated dissection. This was not present on imaging during his initial hospitalization. The patient underwent successful endovascular management. Discussion: Visceral artery aneurysms are rare and when identified often require early intervention. Posttraumatic etiologies are often due to penetrating trauma as in the case presented. Modern high resolution imaging can identify those that are not yet symptomatic. Conclusion: Posttraumatic visceral artery aneurysms are rare with an incidence of 0.01–0.2%, however they have a potential for high mortality if undiagnosed or untreated. An aggressive operative approach can lead to favorable outcomes.